What Factors Influence Users to Install a Photography-Category Application to Their Android Smartphone - Dermawi, Rizdania; Tolle, Herman (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Availability of the various kinds of Android applications provide the users to get any mobile application that can support their daily activities, whether it supports the work or other needs. Too many applications available often confuse the user to make a decision which application they have to install to their smartphone. This study analyzes the factors that may influence users to make a decision whether or not installing a particular application from photography-category in Play store. The result obtained that users decide to install significantly affected by internal factors (user’s internet quota, user’s smartphone specification) and also significantly affected by an external factor (rating, review, advertisement and friend’s recommendation).